Better Understanding the Workers' Retirement Decision Attitudes: Development and Validation of a New Measure - Fouquereau, Evelyne; Bosselut, Grégoire; Chevalier, Séverine; Coillot, Hélène; Demulier, Virginie; Becker, Caroline; Gillet, Nicolas (Frontiers in Psychology, 2018)
The aim of the present research was to develop a measure that could be used in future research for in-depth study of the psychological management of retirement. We report the results of six studies involving 1,898 French workers designed to develop and assess the psychometric properties of a new instrument named the Workers' Retirement Motivations Inventory (WRMI) using the push pull anti-push anti-pull model. The items were constructed based on a review of the relevant psychological literature and face-to-face interviews with senior workers. A combined method of exploratory structural equations modeling and confirmatory factor analysis (CFA) was employed and provided evidence for validating this structure of the inventory. The WRMI showed consistency of the four-factor structure across different samples, internal consistency, test-retest reliability, and predictive validity of workers' plans for retirement. Implications of these findings and avenues for counseling activities and future research are discussed.